2012
DOI: 10.1016/j.ejvs.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Early Results from the ENGAGE Registry: Real-world Performance of the Endurant Stent Graft for Endovascular AAA Repair in 1262 Patients

Abstract: Early results from this real world, global experience are promising and indicate that endovascular AAA repair with the Endurant Stent Graft is safe and effective across different geographies and standards of practice. Longer-term follow-up is necessary to assess durability of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 18 publications
5
108
1
2
Order By: Relevance
“…The rate of reintervention for limb occlusion was low (0.7% within 30 days and 1.1% through 1 year) compared to earlier reports preceding the initiation of the EVAS FORWARD Global registry, 5 likely attributable to learning curve and development of procedural best practices around optimization of the flow lumen. The overall reintervention and aneurysm-related mortality rates in the EVAS FORWARD registry appear to be broadly similar to those described in large EVAR registries 8,9 but in a more anatomically challenging patient cohort.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The rate of reintervention for limb occlusion was low (0.7% within 30 days and 1.1% through 1 year) compared to earlier reports preceding the initiation of the EVAS FORWARD Global registry, 5 likely attributable to learning curve and development of procedural best practices around optimization of the flow lumen. The overall reintervention and aneurysm-related mortality rates in the EVAS FORWARD registry appear to be broadly similar to those described in large EVAR registries 8,9 but in a more anatomically challenging patient cohort.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study the 12-month all-cause mortality was 5.2%, which is lower than the 7.4% reported in the ENGAGE registry. 8 This finding can be regarded as of only marginal interest at present due to the small number of patients, different period of recruitment, and short follow-up, but a continuing trend of this nature might prompt a comparative evaluation of EVAR and EVAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENGAGE study of 1262 patients (approximately one-fifth outside IFU) oversized 20% with respect to the inner vessel diameter reported with no stent migration at 1 year and with satisfactory outcomes [42]. Pitton et al showed strong results after 10-year follow-up with 20-25% oversizing of proximal diameters and 10-15% oversizing distally [73].…”
Section: Recent Sizing Our Experience Conclusionmentioning
confidence: 88%
“…In fact, migration following the EVAR has been reported in many studies with rates ranging from 0% to 45%, varying with different patient populations, follow-up times, and stent-grafts used [25,[41][42][43]. Migration can occur for a number of reasons, but can be best understood in the context of the biomechanical forces.…”
Section: Graft Migrationmentioning
confidence: 99%